Spontaneous nanoemulsification for solubility enhancement of BCS class II and IV molecules, quercetin as a model drug - Marwan Motuq Alsufyani; Waleed Mohammad Alqarni; Yousef Alzahrani; Alaa Khalid Balbed; Musab Musleh Alkathyri; Mohammed Akhlaquer Rahman (MethodsX, 2025)
Spontaneous emulsification represents a practicable and efficient method for the formulation of nanoemulsion utilized in drug delivery systems. This method provides numerous advantages, such as increased energy efficiency optimization, the possibility of scaling up for industrial use, enhanced drug loading capacity, and safeguarding sensitive compounds designated for encapsulation. Nanoemulsion can be produced simply by combining water, oil, surfactant, and co-surfactant in specific ratios. The sequence in which these components are mixed is generally regarded as non-critical, as nanoemulsions form spontaneously. However, despite the spontaneous nature of nanoemulsification, the forces driving this process are minimal, and the time required for these systems to achieve equilibrium can be considerable. The titration method employed for developing the phase diagram, along with the selection of nanoemulsions from the constructed phase diagram, is crucial for researchers. The objective of this study is to understand the feasibility of this method to prepare nanoemulsion using quercetin as model drug. Overall, • This method resulted in development of efficient screening technique for nanoemulsion. • Validation was achieved by measuring droplet size and drug release confirmed the usefulness of the method. • This approach presents a cost-effective method applicable in drug design to enhance its solubility and thus bioavailability.